High Protein Diet Ameliorates the Reprotoxic Effects in Male Swiss Albino Mice Exposed to Electromagnetic Radiation Emitted from Mobile Phone - Debajyoti Bhattacharya; Prerona Biswas; Somnath Gangopadhyay; Mausumi Sikdar (ne'e Bhakta) (Wolters Kluwer Medknow Publications, 2020)
Background & Objectives: In modern times, dependence on mobile phones has skyrocketed and so has the susceptibility to be exposed to its irradiated electromagnetic waves that culminate its fatal effects on different physiological systems, even on the male reproductive system. This study investigated whether the adverse effects caused by mobile phone radiation on male albino mice can be mitigated by a high protein diet (HPD). Methodology: Male Swiss Albino mice (n=24) were administered a standard laboratory diet (Groups A & B) or HPD, fortified with 20% casein (Groups C & D) and Groups A (n=6) and D (n=6) served as controls. Animals of Groups B (n=6) and C (n=6) were exposed to electromagnetic radiation, GSM like frequencies of 1.8 GHz emitted from the mobile phone (Micromax Bharat 2; Q 402), connected with a power meter with a specific absorption rate 1.6W/kg for 3 hours continuously per day for 3 months on the exposed groups. The animals were sacrificed after the exposure period & the tissues were weighed and collected for the histology; sperm was isolated for total count, motility and viability assays, and ultrastructural analysis. Results: Total number of sperm and the weights of the testicular tissues and the other accessory sex organs are markedly altered with respect to the control when exposing to the E.M.R of mobile phone. The structure of the sperm was distorted as assessed by scanning electron microscopy, the motility (progressive and non-progressive), and viability of the sperms were severely compromised on exposure to E.M.R. Histological analysis of testicular tissues showed distorted morphology and cellular disorientation on radiation exposure. Signs of improvement in all these parameters were recorded in the group exposed to E.M.R. and supplemented with HPD. Conclusion: The use of mobile phones drastically impacts the reproductive functions and casein enriched HPD proved its efficacy in preventing these detrimental effects of electromagnetic radiation of mobile phones in male mice.